Determination of structural and mechanical properties, diffractometry, and thermal analysis of chitosan and hydroxypropylmethylcellulose (HPMC) films plasticized with sorbitol - Rotta,Jefferson (2011)
In this work, the structural, mechanical, diffractometric, and thermal parameters of chitosan-hydroxypropylmethylcellulose (HPMC) films plasticized with sorbitol were studied. Solutions of HPMC (2% w/v) in water and chitosan (2% w/v) in 2% acetic acid solution were prepared. The concentration of sorbitol used was 10% (w/w) to both polymers. This solutions were mixed at different proportions (100/0; 70/30; 50/50; 30/70, and 0/100) of chitosan and HPMC, respectively, and 20 mL was cast in Petri dishes for further analysis of dried films. The miscibility of polymers was assessed by X-ray diffraction, scanning electronic microscopy (SEM), differential scanning calorimetry (DSC), and thermal gravimetric analysis (TGA). The results obtained indicate that the films are not fully miscible at a dry state despite the weak hydrogen bonding between the polymer functional groups.